New models of care for a local district general hospital - Mears, Paul (Future Hosp J, 2015)
There is an increasing realisation that new care models will be required to deliver healthcare to an increasingly elderly and complex patient population. District general hospitals (DGH), particularly those in rural locations, have a key part to play in providing care to their local population, but there is a growing realisation that the DGH model will need to evolve considerably to be financially and clinically sustainable in the future. NHS England's Five year forward view has established a number of options for new models of care, and health communities around the country have been selected as vanguard sites to pilot these new care models. Yeovil District Hospital has been working for two years in primary care, social care and community services in the Symphony Project to develop an integrated care model which will proactively manage the care of the most complex patients. The model has been selected as a vanguard site and the hospital is developing a new model which has the potential to be adopted by other smaller local district hospitals.